Preserving Farmlands: A Land Use Land Cover Analysis of the Agricultural Land Reserve in Metro Vancouver - Gemino, Christina; Soma, Tammara; Bodnar, Chris (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2026)
The Agricultural Land Reserve (ALR) has been identified as an important planning tool to prevent non-farm uses on agricultural land and thus sustain agricultural activities in the region. Using a land use land cover (LULC) analysis of Metro Vancouver's Agricultural Land Use Inventory data from 2016 and 2022, this study evaluates land use changes in the provincially protected ALR. In our study we found a 3.2% decline in cultivated land, coupled with a 121% increase in non-farm industrial use, with 42% of all new homes built within the protected areas being estate homes. The paper provides an update to Metro Vancouver’s 2014 comprehensive land use assessment of agricultural land, and argues that regular monitoring of land use patterns in the ALR can better support its mandate. These findings suggest the need for future research to explain the drivers behind the increase in non-farm use in the agricultural protected area of Metro Vancouver.